Radiosynthesis and 'click' conjugation of ethynyl‐4‐[18F]fluorobenzene — an improved [18F]synthon for indirect radiolabeling. (3rd November 2015) - Roberts, Maxine P.; Pham, Tien Q.; Doan, John; Jiang, Cathy D.; Hambley, Trevor W.; Greguric, Ivan; Fraser, Benjamin H.
Abstract : Reproducible methods for [ 18 F]radiolabeling of biological vectors are essential for the development of new [ 18 F]radiopharmaceuticals. Molecules such as carbohydrates, peptides and proteins are challenging substrates that often require multi‐step indirect radiolabeling methods. With the goal of developing more robust, time saving, and less expensive procedures for indirect [ 18 F]radiolabeling of such molecules, our group has synthesized ethynyl‐4‐[ 18 F]fluorobenzene ([ 18 F]2, [ 18 F]EYFB) in a single step (14 ± 2% non‐decay corrected radiochemical yield (ndc RCY)) from a readily synthesized, shelf stable, inexpensive precursor. The alkyne‐functionalized synthon [ 18 F]2 was then conjugated to two azido‐functionalized vector molecules via CuAAC reactions. The first 'proof of principle' conjugation of [ 18 F]2 to 1‐azido‐1‐deoxy‐ β ‐d ‐glucopyranoside (3) gave the desired radiolabeled product [ 18 F]4 in excellent radiochemical yield (76 ± 4% ndc RCY (11% overall)). As a second example, the conjugation of [ 18 F]2 to matrix‐metalloproteinase inhibitor (5), which has potential in tumor imaging, gave the radiolabeled product [ 18 F]6 in very good radiochemical yield (56 ± 12% ndc RCY (8% overall)). Total preparation time for [ 18 F]4 and [ 18 F]6 including [ 18 F]F − drying, two‐step reaction (nucleophilic substitution and CuAAC conjugation), two HPLC purifications, and two solid phase extractions did not exceed 70 min. The radiochemical purity of synthon [ 18 F]2 and the conjugated products, [ 18 F]4 and [ 18 F]6, were all greater than 98%. The specific activities of [ 18 F]2 and [ 18 F]6 were low, 5.97 and 0.17 MBq nmol −1, respectively. Abstract : A new [ 18 F]radiosynthon, [ 18 F]ethynyl‐4‐fluorobenzene ([ 18 F]EYFB), has been prepared for the indirect radiolabeling of sensitive molecules that are not amenable to standard radiolabeling conditions. [ 18 F]EYFB was alkyne functionalized for use in 'click' chemistry, which was prepared in adequate yield and high purity from a single step using a readily synthesized inexpensive precursor. The utility of [ 18 F]EYFB was investigated by 'click' conjugation to two azido‐functionalized molecules (a glucose and matrix‐metalloproteinase derivative). The radiochemical purity of [ 18 F]EYFB and the conjugated products were all ≥99%.